Evaluation of an attenuated chicken-origin Histomonas meleagridis vaccine for the prevention of histomonosis in chickens - Chen, Qiao-Guang; Kong, Ling-Ming; Rong, Jie; Chen, Chen; Wang, Shuang; Hou, Zhao-Feng; Liu, Dan-Dan; Tao, Jian-Ping; Xu, Jin-Jun (Frontiers in Veterinary Science, 2024)
IntroductionHistomonosis, a protozoan disease caused by Histomonas meleagridis, poses a significant economic burden on domestic poultry in China. To reduce the losses caused by this disease in chickens, an attenuated vaccine was developed by exploiting the diminished virulence of H. meleagridis through successive in vitro passages.MethodsFour experiments were conducted to evaluate the viability of attenuated H. meleagridis as a potential vaccine candidate. Experiment 1 evaluated the route of infection (oral vs. intracloacal) and dose (5 × 104, 1 × 105, and 2 × 105H. meleagridis/chicken) using the virulent strain H. meleagridis JSYZ-D10. Experiment 2 evaluated the attenuated effect of the H. meleagridis JSYZ-D168 strain (infection dose: 2 × 105H. meleagridis/chicken). Experiment 3 evaluated the immunoprotective effect of different immunization doses (5 × 104, 1 × 105, and 2 × 105H. meleagridis/chicken). Experiment 4 evaluated the immunoprotective effect of different immunization schedules (immunization at 3 days of age; immunization at 14 days of age; two immunizations, one at 3 days of age and one at 14 days of age; immunization and infection dose: 2 × 105H. meleagridis/chicken).ResultsThe results showed that the intracloacal route of infection was more effective and stable compared to the oral route. The pathogenicity of the JSYZ-D168 H. meleagridis strain was significantly reduced compared to the original virulent strain. Chickens vaccinated by intracloacal immunization at a dose of 2 × 105H. meleagridis/chicken on day 14 provided effective protection against a virulent strain challenge, significantly resulting in increased body weight and reduced lesions in the cecum and liver within 28 days post-immunization (p < 0.05). Poor immunoprotection was obtained either when the immunization dose was 1 × 105H. meleagridis/chicken or when the immunization program was a single immunization at 3 days of age only.DiscussionIn conclusion, the administration of a vaccine provides a measurable degree of protection against the detrimental effects induced by H. meleagridis, thus warranting its endorsement in clinical settings.